ANALISIS ESG TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BEI MELALUI SYSTEMATIC LITERATURE REVIEW - Muthia Marchelizi (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) on stock performance and identify research gaps through a Systematic Literature Review (SLR) approach. This study utilized fifteen scientific articles selected based on inclusion criteria and relevant to companies listed on the Indonesia Stock Exchange (IDX). The analysis revealed that the relationship between ESG and stock performance lacks clear consistency. The research findings fall into three main categories: positive, insignificant, and negative, particularly in the short term. These differences in results are influenced by various factors, such as the observation period, industry sector characteristics, company size, ESG measurement methods, and the indicators used to assess stock performance. Furthermore, implementing ESG generally requires significant initial costs, so its benefits tend to be more pronounced in the long term. Theoretically, the relationship between ESG and stock performance can be explained through stakeholder theory, signaling, and legitimacy. Implementing ESG can increase investor confidence, provide positive signals regarding a company's prospects, and strengthen its legitimacy in the public eye. Therefore, while ESG may have a detrimental impact in the short term, in the long term, this practice has the potential to increase company value and stock performance